2009
DOI: 10.1021/jp9010108
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulations of Film Rupture in Water/Surfactant Systems

Abstract: Molecular dynamics simulation has been performed on water/surfactant film rupture in order to investigate foam stability. A periodic boundary film model which was simulated in a lateral dimension of 8 x 8 nm(2) for 4 ns was established to stand for a part of a foam bubble. On the basis of critical film thickness, which is the lowest thickness before film rupture, a stability index was calculated to describe the capabilities of surfactants to stabilize water films. We investigated the influence of film size and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
47
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(50 citation statements)
references
References 52 publications
3
47
0
Order By: Relevance
“…Most computer simulations of SDS-NBFs have focused so far on the investigation of the structure of foam films. 10,11,[21][22][23][24][25][26] The simulated structures, with thicknesses similar to those inferred from x-ray experimental data, 17 indicate that the film contains between two and four water molecules per surfactant. Part of this water accumulates around the head groups as solvation water, the remaining distributing in the film's core.…”
Section: Introductionsupporting
confidence: 58%
“…Most computer simulations of SDS-NBFs have focused so far on the investigation of the structure of foam films. 10,11,[21][22][23][24][25][26] The simulated structures, with thicknesses similar to those inferred from x-ray experimental data, 17 indicate that the film contains between two and four water molecules per surfactant. Part of this water accumulates around the head groups as solvation water, the remaining distributing in the film's core.…”
Section: Introductionsupporting
confidence: 58%
“…Gamba and coworkers [25] made an attempt to use MD to simulate the air/liquid interface with the same composition as that in the experiments of Benattar et al [26]. Yang et al [27] used MD simulation to investigate water/surfactant film rupture to predict the stability of films. The increment of both the lateral dimension and the duration of the film will lead to increases in the critical thickness of the film; these investigators found that the former plays a more significant role in film rupture.…”
Section: Introductionmentioning
confidence: 99%
“…Several works have reported classical computer simulation investigations of SDS black film foams 10,18,[21][22][23][24][25] . Simulation studies indicate that the equilibrium film contains between two and four water molecules per surfactant, and between two and three of these molecules are part of a solvation layer.…”
Section: Introductionmentioning
confidence: 99%